Demand-Driven E-book Program in Tallinn University of Technology Library: The First Two Years of Experience with the EBL Platform. (2nd April 2016) - Kont, Kate-Riin
ABSTRACT: The ease and effectiveness of patron-driven (demand-driven) acquisitions has helped to optimize many academic libraries' acquisitions budgets. Libraries are increasingly turning to e-books as an alternative to purchasing multiple copies. Academic libraries have for years been forced to purchase large packages of e-books that are of questionable financial value because so much of the content is not used. The number of content units downloaded from large e-book packages by university patrons is not growing. At the same time, the number of checkouts of print books is declining. Advantages of e-books over print are discussed. Also mentioned are a few drawbacks, particularly the fact that European Union countries impose a higher level of value-added tax (VAT) on them than on print books. The author presents a case study analyzing the first two years of experience with the Ebook Library (EBL) platform at the Tallinn University of Technology Library, giving an overview of the advantages and successful measures of demand-driven acquisition in the form of short-term loans.